A comparative study of the cytotoxic effect of chlorogenic acid on BM-12 cells from Bombyxmori (insect) and Mammalian cell line (Funded work) - ARCHANA MOON,; AMIT TAKSANDE,; PUNYASHA SAMAL,; VAIJAYANTI CHAHANDE,; PRASHANT CHAVHAN,; MANOJ RAI, (International Journal of Pharma and Bio Sciences, 2017)
Mammalian cell lines are routinely used to study the effect of various drugs However working on human cell lines is expensive and is associated with problems like slow growth rate and contamination. Using insect cells as an option for cancer research is more cost effective, easy to handle, and the culture conditions are relatively facile. The main objective of this study was to check the effect of chlorogenic acid, a phytochemical, on Bm12 cell line and PA-1 cell line and compare its cytotoxicity on both cell lines. For this Bm12 cells were treated with 100, 300 and 500µM CGA and cell viability was assessed at every 2 hr interval for 10 hrs using trypan blue dye exclusion assay. PA-1 cells were treated with different concentrations of CGA ranging from 50-500µM and cytotoxicity was determined using MTT assay. Cisplatin, a standard drug for ovarian cancer, was used as standard for comparing cytotoxicity. It was observed that the cell viability decreases with increasing concentration of CGA. Transformed cells were found to be more sensitive to CGA as compared to Bm12 cells, which suggests that cytotoxicity of CGA is more specific to transformed or cancer cells as compared to normal, non-transformed cells. Around 50% cytotoxicity of PA-1 cells is observed using CGA of higher concentrations (500µM), which indicates that CGA is a better alternative to Cisplatin. Results indicate that, at higher concentration of CGA, cytotoxic effect was much faster in Bm12 cells than PA-1 cells. Thus, it can be concluded that Bm12 cells can be used to determine cytotoxicity of any anticancer compound, much readily and easily.